Impact of cardiovascular risk stratification strategies in kidney transplantation over time. Issue 10 (6th October 2020) - Deak, Andras T; Ionita, Francesca; Kirsch, Alexander H; Odler, Balazs; Rainer, Peter P; Kramar, Reinhard; Kubatzki, Michael P; Eberhard, Katharina; Berghold, Andrea; Rosenkranz, Alexander R
Abstract: Background: Kidney transplant recipients exhibit a dramatically increased cardiovascular (CV) risk. In 2007, Austrian centres implemented a consensus of comprehensive CV screening programme prior to kidney transplantation (KT). The consensus placed a particular emphasis on screening for coronary artery disease (CAD) with cardiac computed tomography (CT) or coronary angiography (CAG) in patients with diabetes mellitus, known CAD or those having multiple conventional CV risk factors. Here, we investigate if this affected risk stratification and post-transplant CV outcomes. Methods: In a retrospective chart review, we evaluated 551 KTs performed from 2003 to 2015 in our centre. Patients were categorized into three groups: KT before (2003–07), directly after (2008–11) and 5 years after (2012–15) implementation of the consensus. We analysed clinical characteristics, the rate of cardiac CTs and CAGs prior to KT as well as major adverse cardiac events (MACEs) during a 2-year follow-up after KT. Results: The three study groups showed a homogeneous distribution of comorbidities and age. Significantly more cardiac CTs (13.6% versus 10.2% versus 44.8%; P = 0.002) and CAGs (39.6% versus 43.9% versus 56.2%; P = 0.003) were performed after the consensus. Coronary interventions were performed during 42 out of 260 CAGs (16.2%), the cumulative 2-year MACE incidence was 8.7%. Regarding MACE occurrence, no significant difference between the three groups was found. Conclusion: CV risk stratification has become more rigorous and invasive after the implementation of the consensus; however, this was not associated with an improvement in CV outcome.